2020
DOI: 10.18231/2581-3706.2018.0061
|View full text |Cite
|
Sign up to set email alerts
|

Study of platelet indices in hyperlipidemia

Abstract: Introduction: Atherosclerosis is a chronic inflammatory condition n resulting from hyperlipidemia and involves platelet mediated recruitment of white blood cells to arteries. The platelet activation is measured indirectly through several platelet indices routinely available without any additional cost in newer fully automated haematology analysers. These indices include platelet count, mean platelet volume(MPV), platelet distribution width(PDW), plateletcrit(PCT), mean platelet(component) concentration (MPC), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
2
1
1
Order By: Relevance
“…Hence, we have conducted a present case-control study with both age and sex-matched controls to keep away such bias in our results. In our study, we observed a male-to-female ratio of 1.5:1 among cases which correlates with the study done by Khemka and Kulkarni and Hawaldar and Sodani [ 14 - 15 ].…”
Section: Discussionsupporting
confidence: 92%
“…Hence, we have conducted a present case-control study with both age and sex-matched controls to keep away such bias in our results. In our study, we observed a male-to-female ratio of 1.5:1 among cases which correlates with the study done by Khemka and Kulkarni and Hawaldar and Sodani [ 14 - 15 ].…”
Section: Discussionsupporting
confidence: 92%
“…and discordance to Hawaldar R. et al and Khemka R et al Female preponderance in the present study could be due to most of the females visiting the hospital in their 5 th decade of life, increased sedentary life, smoking, and various hormonal imbalances. The maximum number of patient in the present study were in the 41-60 years age group which correlate with the study of Hawaldar R. et al and Janani K et al 13,14 Age was not found to be statistically significant in both the groups. However, hyperlipidemia in younger children may be due to familial hypercholesterolemia and the popularity of fast food consumption among the young age groups.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, in relation to DL, in the cohort studied by Singh et al., there was a positive association between DL and MPV, but nonsignificant results were found regarding PCT 45 . In contrast, other studies with considerably larger cohorts reported a positive association between LDL/VLDL cholesterol and PCT and PLA, but no association with MPV was reported 46,47 . Given our paradoxical findings, we should note that 59.5% of dyslipidaemic patients in our cohort were treated with statins and, therefore, did not present a significant increase in LDL cholesterol levels.…”
Section: Discussioncontrasting
confidence: 70%
“…45 In contrast, other studies with considerably larger cohorts reported a positive association between LDL/ VLDL cholesterol and PCT and PLA, but no association with MPV was reported. 46,47 Given our paradoxical findings, we should note that 59.5% of dyslipidaemic patients in our cohort were treated with statins and, therefore, did not present a significant increase in LDL cholesterol levels. In addition, it has been stated that the use of statins can affect MPV.…”
Section: Discussionmentioning
confidence: 73%